Karakter Shared Street pada Jalan-jalan di Perkampungan Krapyak Kulon - Mohammad Ibnu Saud (Universitas Lambung Mangkurat, 2007)
Krapyak Kulon is one of the kampong in Yogyakarta which is similar with the other kampongs. Uniquely, it has three name of the street types at there, they are Jalan Rukun, Jalan Pertolongan and Gledekan.These kind of streets are part of the shared street. Shared street or integrated street on the dwelling area is a type of street which is suitable with the physical and social dwelling environment. Generally it is used for traffic, social interaction and daily activities. Shared street triggers new design configuration which increase social interaction, street safety, and pedestrian movement. Shared street concept is one of the important concept in dwelling area design.Street with shared street type can be found in many part of the world with its own name and character. Shared street in Krapyak Kulon also has its own name and character. By knowing the character of the shared street in krapyak Kulon, it will give a good description the suitable character for the design of dwelling area in Indonesia.